Effect of Elevated CO2 on the Growth of Two Different Climate-origin Forbs in Four Levels of Nitrogen Nutrition - Okuda, Toshinori; Mariko, Shigeru; Furukawa, Akio (Universiti Putra Malaysia Press, 1995)
Two different climate-origin forbs, Chenopodium album L. (native to temperate regions) and Amaranthus patulus Benol (native to neo-tropical regions), were grown in growth chambers at two CO2 levels, 350 and 700 ppm, under [our levels of nitrogen nutrition. Elevated CO2 resulted in increased total biomass and decreased leaf-nitrogen concentration in C. allmm. A decrease in specific leaf area (SLA) was observed with C. album in enriched C0'l' but not in A. patulus. There were no apparent CO2 effects on the growth of A. patulus, but CO2 effects on the growth of C. album were amplified as the nutrient level increased. There was no significant change in allocation between the top (shoot) and root of either species in relation to CO~ enrichment. At present, the two species are co-existing in the eutrophic soil conditions of early successional stages, such as in waste or abandoned fields. However, under elevated CO2 conditions, C. album will probably increase its relative dominance and distribution while A. patulus wiII not. The results imply that the effects of CO2 level on the plants will depend on their climatic origins.